2009
DOI: 10.1111/j.1399-0012.2009.01078.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary venous obstruction after lung transplantation. Diagnostic advantages of transesophageal echocardiography

Abstract: Pulmonary venous vascular complications after lung transplantation are rare and a major cause of morbidity and mortality unless diagnosed and treated early. The epidemiological, diagnostic, and management characteristics of 33 patients (two of them in our hospital) with post-transplant pulmonary vein obstruction published in the literature were reviewed. We consider of utmost importance to differentiate stenosis from thrombosis as the cause of the obstruction. The angiography, considered the gold standard for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 16 publications
0
27
0
1
Order By: Relevance
“…It is unclear why the stenosis appeared more rapidly in these patients, although some cases reported technical difficulties during the surgery itself that were related to anatomic challenges. González-Fernández et al suggest that transesophageal echocardiography (TEE) is a useful, noninvasive imaging modality that can rapidly identify postoperative anastomotic compromise, as rapid identification of PVS by TEE can allow for rapid surgical intervention, avoiding a delay in diagnosis and management [ 10 ]. Michel-Cherqui et al also found utility in the use of TEE intraoperatively during lung transplantation surgery itself, as it allowed measurements of peak systolic flow velocity in the pulmonary vein and, if elevated, the pressure gradient across the anastomosis, to allow immediate identification and correction of the PVS [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear why the stenosis appeared more rapidly in these patients, although some cases reported technical difficulties during the surgery itself that were related to anatomic challenges. González-Fernández et al suggest that transesophageal echocardiography (TEE) is a useful, noninvasive imaging modality that can rapidly identify postoperative anastomotic compromise, as rapid identification of PVS by TEE can allow for rapid surgical intervention, avoiding a delay in diagnosis and management [ 10 ]. Michel-Cherqui et al also found utility in the use of TEE intraoperatively during lung transplantation surgery itself, as it allowed measurements of peak systolic flow velocity in the pulmonary vein and, if elevated, the pressure gradient across the anastomosis, to allow immediate identification and correction of the PVS [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…7 Timely diagnosis and correction of this condition intraoperatively mitigates postoperative hemodynamic decompensation, graft failure, and death. 6,8 The routine use of TEE during lung transplant is increasing but remains unendorsed by the Society of Cardiovascular Anesthesiologists and the American Society of Echocardiography. As the number of lung transplantations performed continues to rise with the growing donor pool of ex vivo lung perfusion organs, standardizing the use of TEE for lung transplantation is paramount.…”
Section: Pulmonary Vein Velocities: a Useful Tool For Cardiac Anesthementioning
confidence: 99%
“…Pulmonary venous obstruction is rare, occurring in 0.4 to 2.7% of lung transplants. 152,153 The use of an atrial cuff for the venous anastomosis makes it easier to orient in comparison to an arterial anastomosis, and therefore is generally less prone to complications. Clinical manifestations of pulmonary venous obstructions include hypoxia, pulmonary edema, hemoptysis, hemodynamic instability, and poor response to inotropic agents.…”
Section: Vascular Complicationsmentioning
confidence: 99%